Temporal changes and correlates of tobacco and E-cigarettes use among school-going students in Albania: insights from global youth tobacco surveys (2015-2020) - Dadras, Omid (SPRINGER, 2025)
Tobacco use often starts during adolescence, with many adults beginning before 21. This study investigated the patterns and factors associated with tobacco and e-cigarette use among school-aged adolescents in Albania. Data were analyzed from two Albania Global Youth Tobacco Surveys (GYTS) conducted in 2015 and 2020. Participants included 7th-10th grade students (ages 12-16) who completed the survey (n = 9985). Descriptive statistics depicted demographic characteristics, tobacco, and e-cigarette use across survey years. Logistic regression assessed temporal changes and the odds of use across independent variables, adjusting for age and sex. From 2015 to 2020, tobacco and e-cigarette use among students aged 13-15 increased from 12.86 to 14.49% and from 6.8 to 8.8%, respectively. Cigarette smoking declined from 8.4 to 4.3%, but the use of other tobacco products nearly doubled, from 6.4 to 12.3%. Higher odds of use were found among males, older students, and those with more pocket money. Environmental factors like family, peer, and media exposure to smoking increased the likelihood of use. Anti-tobacco messages had no significant impact, while advertising strongly influenced usage. Knowledge of tobacco harms and anti-smoking attitudes correlated with lower odds of use. Increased availability of cigarettes near schools was linked to higher odds of tobacco use. The study highlights gaps in anti-tobacco messaging and the strong influence of advertising, underscoring the need for targeted and effective tobacco control strategies in Albania.